2017
DOI: 10.1037/pha0000124
|View full text |Cite
|
Sign up to set email alerts
|

Does menthol cigarette use moderate the effect of nicotine metabolism on short-term smoking cessation?

Abstract: The nicotine metabolite ratio (NMR) has been shown to predict response to the transdermal nicotine patch, such that faster nicotine metabolism is associated with a lower abstinence rate. Menthol cigarette use, vs. non-menthol cigarette use, slows nicotine metabolism and therefore may attenuate the effect of NMR on smoking abstinence. In this study, we evaluated whether cigarette type (menthol vs. non-menthol) modified the association between NMR and short-term abstinence. This was a secondary analysis examinin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…This is notable as White smokers are less likely to smoke menthol cigarettes, which have been shown to inhibit nicotine metabolism and thus may lower the NMR. 26,27 However, previous work by Jao et al 28 suggests that menthol cigarette use was not associated with short-term smoking abstinence, and there was no evidence of an interaction between cigarette type and NMR on the effect of short-term abstinence.…”
Section: Discussionmentioning
confidence: 91%
“…This is notable as White smokers are less likely to smoke menthol cigarettes, which have been shown to inhibit nicotine metabolism and thus may lower the NMR. 26,27 However, previous work by Jao et al 28 suggests that menthol cigarette use was not associated with short-term smoking abstinence, and there was no evidence of an interaction between cigarette type and NMR on the effect of short-term abstinence.…”
Section: Discussionmentioning
confidence: 91%
“…Of these, 22 met all study inclusion criteria. 8,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][40][41][42][43][44] In three instances, two published articles analyzed data from the same underlying study; therefore, our meta-analysis included information from 19 data sources representing 147 584 cigarette smokers. Although we did not intentionally exclude non-US studies, all identified studies except for one were conducted exclusively in the United States, and the one exception included smokers from both the United States and Canada.…”
Section: Search Resultsmentioning
confidence: 99%
“…Longitudinal studies of exposure markers have primarily been secondary analyses of randomized controlled clinical trials (RCTs) or non-randomized studies of smoking cessation, and thus offer an opportunity to look at potential predictive relationships with treatment response. One such secondary analysis of a 8-week RCT of nicotine replacement therapy (NRT), in the form of a 21mg/day transdermal nicotine patch, measured the impact of NMR at baseline on treatment response in 474 smokers (22). Those with a lower NMR (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…This systematic review yielded many study studies revealing associations between peripheral biomarkers and clinical outcomes, most notably: severity of dependence, treatment response, and risk of relapse after cessation. Biomarkers of exposure such as cotinine, beyond indicating smoking status, showed robust associations with severity of dependence (30-32, 40), and low NMR showed an association with increased risk of relapse during cessation (22, 35). Cotinine showed less consistent associations with CPD, suggesting expired CO as a superior status marker and cotinine/NMR a superior dependence marker.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation